Middle Managerial Capability, Teamwork Dan Performance: Studi Peran Leader Gender - Proboningrum, Angga Atma; Suhariadi, Fendy (Jurnal Ilmu Manajemen, 2024)
The background to this research is based on the fact that the Republic of Indonesia Police organisation views the existence of women and children as important. This is demonstrated by forming the Directorate of Women and Children Services (PPA). Empirically, women's leadership in all processes positively impacts organisational performance. For this reason, what is of concern in this research is women's leadership as an answer to the complexity of the East Java Regional Police's PPA work. This research aims to urgently carry it out considering the high number of PPA cases in the East Java Regional Police to test the role of middle managers' capabilities in shaping performance through teamwork with gender leadership mechanisms. The methodology used is quantitative research with a survey approach using census techniques. The results of testing the interaction of leader gender as a moderator variable are shown by an interaction coefficient value of -0.189, with a p-value of 0.003 <0.05. Thus it can be said that leader gender influences the magnitude of the influence of middle managers' managerial ability (MMC) on teamwork (TMW). The implementation of the research results can be conveyed that the smaller the leader's gender (female leader), the stronger the influence of middle manager capabilities on teamwork.